Subgaleal Effusion and Brain Midline Shift After Cranioplasty: A Retrospective Study Between Polyetheretherketone Cranioplasty and Titanium Cranioplasty After Decompressive Craniectomy - Ji, Tao; Yao, Peiwen; Zeng, Yu; Qian, Zhouqi; Wang, Ke; Gao, Liang (Frontiers in Surgery, 2022)
Cranioplasty with polyetheretherketone (PEEK) has recently shown better cerebral protection performance, improved brain function, and aesthetic contour compared with titanium mesh. However, whether patients undergoing PEEK cranioplasty tend to develop subgaleal effusions remains elusive. This retrospective study included patients who underwent cranioplasty with PEEK implants or titanium mesh after decompressive craniectomy between July 2017 and July 2020. Patient information, including general information, location, size of the defect, subgaleal depth, and brain midline shift was collected and statistically analysed. There were 130 cases of cranioplasty, including 35 with PEEK implants and 95 with a titanium mesh. Patients who underwent cranioplasty with a PEEK implant had a higher subgaleal effusion rate than those who underwent cranioplasty with titanium mesh (85.71% vs. 53.68%, P < 0.001), while a midline shift > 5 mm was more frequently observed in the PEEK group than in the titanium group (20% vs. 6.3%, P = 0.021). The PEEK material was the only factor associated with subgaleal effusion after cranioplasty (OR 5.589, P = 0.002). Logistic regression analysis further showed that age was a protective factor against midline shift in the PEEK cranioplasty group (OR 0.837, P = 0.029). Patients who underwent cranioplasty with PEEK implants were more likely to develop severe subgaleal effusion and significant brain midline shifts than those with titanium mesh implants.